Afiksasi verba dalam bahasa Indonesia - Rajeg, GPW; Denistia, K (Agency for Language Development and Cultivation [Badan Pengembangan dan Pembinaan Bahasa], 2023)
Verbal affixation of Bahasa Indonesia (Indonesian [BI]) has been widely discussed in every Indonesian grammar book and theoretical kinds of literature. However, so far, the discussion of the quantitative distribution of BI verbal affixation is still lacking. This chapter offers new insights by presenting a description of the form, function and meaning of verb affixation based on a large collection of Indonesian digital texts (language corpora) of various text varieties in the last ten years. The corpus data is explored to show examples of word formation that were not discussed before, thus enriching the description of the affixation. The quantitative distribution of verb affixation covers the affix productivity (i) in the whole corpus, (ii) by genres, and (iii) diachronically within the last ten years. The productivity of verb affixation shows variations based on text variety. For example, the number of unique words (type frequency) and words found once in the corpus (i.e., hapax legomena) are relatively very low in normative formal varieties such as Legislation and Official Letters, but very high in Short Stories, Novels, and Newspapers. In the last ten years (2011-2020), Indonesian main verb affixations (ME-, DI-, BER-, and TER-) have experienced a downward trend regarding their type frequency and number of hapaxes. Afiksasi verba bahasa Indonesia (BI) telah banyak dibahas dalam setiap buku tatabahasa BI dan literatur-literatur teoretis. Akan tetapi, sejauh ini, pembahasan distribusi kuantitatif afiksasi verba BI masih minim. Makalah ini membawa kebaruan dengan menampilkan deskripsi bentuk, fungsi dan makna afiksasi verba berdasarkan bank data teks digital melimpah (korpus bahasa) dari berbagai ragam teks dalam sepuluh tahun terakhir. Data korpus digali untuk menampilkan contoh-contoh bentukan kata yang tidak dibahas sebelumnya, sehingga memperkaya deskripsi afiksasi tersebut. Selanjutnya, distribusi kuantitatif afiksasi verba yang diulas adalah tingkat produktifitasnya (i) secara menyeluruh, (ii) berdasarkan dimensi ragam teks, dan (iii) secara diakronis dalam rentang sepuluh tahun terakhir. Secara kuantitatif, produktivitas afiksasi verba menunjukkan variasi berdasarkan ragam teks. Misalnya, jumlah kata unik (frekuensi tipe) dan kata yang ditemukan sekali dalam korpus (hapax) secara relatif sangat rendah pada ragam formal normatif seperti Perundang-Undangan dan Surat Resmi, namun sangat tinggi pada Cerpen, Novel, dan Koran. Dalam rentang sepuluh tahun terakhir (2011-2020), afiksasi verba utama BI (ME-, DI-, BER-, dan TER-) mengalami tren penurunan dalam hal frekuensi tipe dan jumlah hapax-nya.